Phase II study of modified FOLFIRINOX for chemotherapy-naïve patients with metastatic pancreatic cancer (MPC) - Ozaka, Masato; Ishii, Hiroshi; Sato, Tosiya; Ueno, Makoto; Ikeda, Masafumi; Uesugi, Kazuhiro; Sata, Naohiro; Miyashita, Kouichirou; Mizuno, Nobumasa; Tsuji, Kunihiro; Okusaka, Takuji; Furuse, Junji (Pancreatology : official journal of the International Association of Pancreatology (IAP) ... [et al.], 2016)
Background: FOLFIRINOX is considered one of the standard chemotherapy regimens for chemotherapy-naïve pts. with MPC, but carries an unfavorable adverse event (AE) profile.